O modelo keynesiano de James Meade - Heller, Claudia [UNESP]; Almeida, Roselaine Bonfim de (Nova Economia, 2012)
Este artigo reavalia o modelo simplificado da Teoria Geral de Keynes elaborado por James Meade e procura complementar alguns dos argumentos teóricos que Meade deixou apenas indicados. O artigo também responde às solicitações de Frisch a Meade, quanto à explicação do significado de estabilidade e à explicitação dos pressupostos que garantem suas conclusões. Além disso, apresenta alguns dos cálculos não desenvolvidos por Meade, e, quando necessário, suas devidas correções.

The paper reassesses the simplified model of Keynes's General Theory developed by James Meade and attempts to complement some of the theoretical arguments that Meade only left indicated. It also answers Frisch's questions to Meade with regard to explanation of the mean of stability and elaboration of the assumptions that support his conclusions. The paper also presents some of the calculations undeveloped by Meade and, when necessary, their corrections.
Keywords: Teoria Keynesiana; Investimento e Poupança; Equilíbrio; Estabilidade; Expectativas; Keynesian theory; Investment and Saving; Equilibrium; Stability; Expectations